Probiotic Contents and Antioxidant Activity in Probiotic Drinks Patikala Fruit Juice (Etlingera Elatior (Jack) R.M.Smith) from Kolaka - Azizah, Nur; Muktafia, Muktafia; Anjarsari, Lisa; Putri, Sartika Gunawan (BIOEDUSCIENCE, 2024)
Background: Patikala fruit (Etlingera elatior) can be used as food, medicine, and to boost the immune system. Patikala is a fruit with a high nutritional value that can be used to make a probiotic drink. The aims of this study were to see if patikala fruit juice could be used as a probiotic and antioxidant drink as an immune booster after the COVID-19 pandemic.. Methods: The patikala fruit used is typical of the Kolaka area. This research used a randomized block design using different fermentation time factors. Each treatment was carried out 3 times repetitions. Making a probiotic drink from patikala (Etlingera elatior) is by taking patikala fruit juice with a mixture of powdered skim milk and Lactobacillus casei bacteria then carrying out fermentation treatment for 20 hours, 24 hours and 28 hours. And a dilution process is carried out to test probiotic levels, and antioxidant activity tests are carried out. Results: The results obtained from the analysis of probiotic contents and antioxidant activity show that the potential of patikala fruit juice to be the best probiotic and antioxidant drink is at a time variation of 28 hours. Because during this time variation, the probiotic contents had reached a maximum total of 9.6 x 1014 cfu/ml with the best ability to ward off free radicals, 9.900% of inhibition. Conclusions: Patikala fruit juice drink (Etlingera elatior) which contains probiotics and potential antioxidant activity as a drink to improve the immune system after the COVID-19 pandemic.